Malaria in Sucre State, Venezuela - Zimmerman Robert H. (Cadernos de Saúde Pública, 2000)
The author reviews the malaria research program in Sucre State, Venezuela, taking an ecosystem approach. The goal was to determine which methods could have been introduced at the onset that would have made the study more ecological and interdisciplinary. Neither an ecosystem approach nor integrated disease control were in place at the time of the study. This study began to introduce an ecosystem approach when two contrasting ecosystems in Sucre State were selected for study and vector control methods were implemented based on research results. The need to have a health policy in place with an eco-health approach is crucial to the success of research and control. The review suggests that sustainability is low when not all the stakeholders are involved in the design and implementation of the research and control strategy development. The lack of community involvement makes sustainability doubtful. The author concludes that there were two interdependent challenges for malaria control: development of an ecosystem approach for malaria research and control, and the implementation of an integrated disease control strategy, with malaria as one of the important health issues.